KEADILAN DALAM POLIGAMI PERSPEKTIF MADZHAB SYAFI’I - Muhammad Mualimur Rifqi; Moh Murtadho; Khoirul Asfiyak (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Polygamy is a discussion in marriage that is most widely debated among experts in Islamic law. Among the scholars who agreed about polygamy there were those who rejected polygamy. People who accept the existence of polygamy assume that the argument in the Koran that Allah commands more than one item, while those who reject the existence of polygamy assume that this is related to gender injustice. In Islam, polygamy is believed to be one solution when a wife cannot give offspring or other social considerations. However, the acquisition of polygamy was required by prioritizing fairness among wives. If you feel that you are unable to do justice, you are prohibited from doing polygamy. Islamic scholars also differ in addressing the meaning of justice in polygamy. Like the Shafi'i School of Law which requires to do justice in polygamy.Key Word : Justice, Polygamy, Madzhab Syafi'i